Characterization of viruses and viroids in Vitis vinifera 'Kyoho' in Hangzhou China by small RNA deep sequencing and molecular detection. Issue 3 (4th May 2021) - Li, Hongmei; Wei, Lingzhu; Qin, Cheng; Cheng, Jianhui; Zhang, Xian; Chen, Weiwei; Lai, Tongfei; Yu, Zhiming; Zhang, Pengcheng; Wu, Jiang; Shi, Nongnong
ABSTRACT: High throughput sequencing of small RNA and RT-PCR revealed that Vitis vinifera 'Kyoho', the main grapevine cultivar in Hangzhou, China, was co-infected with at least three viruses, namely grapevine leafroll-associated virus 3 (GLRaV-3), grapevine geminivirus A (GGVA), and grapevine fleck virus (GFkV), and five viroids, namely hop stunt viroid (HSVd), citrus viroid II (CVd-II), grapevine yellow speckle viroid 1 (GYSVd-1), grapevine yellow speckle viroid 2 (GYSVd-2), and citrus cachexia viroid (CCaVd). Additionally, two new isolates of citrus cachexia viroid, i. e. CCaVd-Kyoho-1 and CCaVd-Kyoho-2, were co-identified. These two isolates consist of 296 and 300 full nucleotides, respectively, with 2.7%–5.0% and 4.6%–6.9% variations individually compared to other CCaVd isolates, and 5.8%–6.1% variations to CVd-II and HSVd in the NCBI database. Point mutations in the form of transitions and transversions, A/T deletions, and A/C insertions were identified. These mutations were mainly distributed in the pathogenic and variation regions. Phylogenetic analysis showed that the two local CCaVd isolates are located in the new evolution clade and could be new members of HSVd in the family Pospiviroidae existing in the grapevine cultivar 'Kyoho'.